1986
DOI: 10.1152/jappl.1986.60.3.1054
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance in exercise-trained rats acclimated at two environmental temperatures

Abstract: The present study was carried out to investigate the effects of exercise training on energy balance in male rats acclimated at two different environmental temperatures. Sedimentary and exercised rats were housed and trained at either 24 or 4 degrees C, with the training program consisting of running on a motor-driven treadmill within their respective environments. After 45 days, energy, protein, and fat contents of rats were determined together with the energy content of food and feces. The results show that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
3
18
1
Order By: Relevance
“…However, food intake of intermittently CA in the present study was not augmented (Table 1) as observed in other studies (HARRI et al, 1984;ARNOLD and RICHARD, 1987). In chronically cold-exposed animals energy intake is generally increased compensatory to increased energy expenditure (HARRI et al, 1984;RICHARD et al, 1986). Fig.…”
Section: Shivering Measurementssupporting
confidence: 79%
“…However, food intake of intermittently CA in the present study was not augmented (Table 1) as observed in other studies (HARRI et al, 1984;ARNOLD and RICHARD, 1987). In chronically cold-exposed animals energy intake is generally increased compensatory to increased energy expenditure (HARRI et al, 1984;RICHARD et al, 1986). Fig.…”
Section: Shivering Measurementssupporting
confidence: 79%
“…In one study, rats exercised on a treadmill for 45 d at either 24 C or 4 C. There was no change in BAT activity or thermogenesis, measured through mitochondrial guanosine 5'-diphosphate binding (GDP) at either temperature. 69 Treadmill exercise training in rats for 33 d also did not affect BAT mitochondrial GDP binding, alter energy expenditure or BAT-mediated thermogenesis. 70 An additional treadmill exercise study in rats indicated that 6 wks of training for 90 min/day, resulted in no change in BAT mass or blood flow, and no change in thermogenic activity.…”
Section: Exercise Does Not Alter Bat Activitymentioning
confidence: 90%
“…2). Some studies have demonstrated increased BAT activity with exercise, [61][62][63][64][65][66] others showed no change in BAT activity, [67][68][69][70] while a third set of studies reported a decrease in BAT activity with exercise. 32,[71][72][73][74] Exercise increases BAT activity Studies in rats have demonstrated that 6-8 wks of swim training for 2-3 hours per day resulted in increased blood flow to BAT and increased responsiveness to norepinephrine stimulation.…”
Section: Exercise Effects On Brown Adipose Tissue Activitymentioning
confidence: 99%
“…It seems probable that the greater energy intake of sedentary cold-exposed rats accounted for most of their extra fat reserve. Appetite suppression has been observed previously in exercised male rats (Arnold, Richard, 1987;Richard, Arnold, Lleblanc, 1986) and, since this phenomenon has not been observed in exercised female rats, is believed to be linked to sex hormones.…”
Section: Discussionmentioning
confidence: 69%
“…The study by Richard et al (1986) has indicated that brown adipose tissue capacity for non-shivering thermogenesis is unimproved by exercise training. However, exercise training, by increasing insulin sensitivity (Berger et al, 1979;Mondon, Dolkas, Reaven, 1980), may prevent the age-related increase in tissue insulin resistance and therefore aid in preserving the brown adipose tissue thermogenesis.…”
Section: Discussionmentioning
confidence: 99%